2020
DOI: 10.3390/ijms21197323
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Core Genes Involved in the Progression of Cervical Cancer Using an Integrative mRNA Analysis

Abstract: In spite of being a preventable disease, cervical cancer (CC) remains at high incidence, and it has a significant mortality rate. Although hijacking of the host cellular pathway is fundamental for developing a better understanding of the human papillomavirus (HPV) pathogenesis, a major obstacle is identifying the central molecular targets involved in HPV-driven CC. The aim of this study is to investigate transcriptomic patterns of HPV-infected and normal tissues to identify novel prognostic markers. Analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Over the past decade, the vast amount of research on the molecular and genetic abnormalities that contribute to CSCC carcinogenesis has substantially expanded, giving an improved insight into the molecular mechanisms of cervical cancer and helping to guide the design of new therapeutic agents. It has been shown that somatic mutations in TP53 [9], PIK3CA [10], KRAS [11], PTEN [12,13], and STK11 [14], as well as some copy number alterations, are relevant to the pathogenesis of cervical cancer [15,16]. The methylation status of EPHX2 and RMI2 was closely related to the prognosis of CSCC [17].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the vast amount of research on the molecular and genetic abnormalities that contribute to CSCC carcinogenesis has substantially expanded, giving an improved insight into the molecular mechanisms of cervical cancer and helping to guide the design of new therapeutic agents. It has been shown that somatic mutations in TP53 [9], PIK3CA [10], KRAS [11], PTEN [12,13], and STK11 [14], as well as some copy number alterations, are relevant to the pathogenesis of cervical cancer [15,16]. The methylation status of EPHX2 and RMI2 was closely related to the prognosis of CSCC [17].…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance, given the significant prevalence of CC in younger age groups compared to other oncological pathologies [ 6 ]. While several studies focused on identifying core factors in the evolution of CC, the genesis of premalignant cervical lesions is not fully unraveled [ 7 , 8 , 9 , 10 ]. CIN represents a condition often identified in young patients of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on molecular and genetic abnormalities predisposing to CSCC carcinogenesis have evolved considerably over the past few decades, providing insight into the molecular processes of cervical cancer and guiding the invention of novel therapeutic agents. Somatic mutations, including KRAS 9 , TP53 10 , PTEN 11 , PIK3CA 12 , STK11 13 , and alterations in gene copy number, are associated with the pathological process of CSCC 14 , 15 . In addition, the methylation of RMI2 and EPHX2 was closely linked to the clinical prognosis of CSCC 16 .…”
Section: Introductionmentioning
confidence: 99%